RATE OF GROWTH IN SPAT AND YEARLINGS OF THE INDIAN BACKWATER OYSTER OSTREA MADRASENSIS PRESTON - Rao, K Virabhadra; Nayar, K Nagappan (Indian Journal of Fisheries, 2015)
Apart from brief reports by Hornell (1910) and Paul (1942) there exists no detailed account of the rate of growth in the Indian backwater oyster, Ostrea madrasensis Preston, which is an important species of shell-fish of commercial value in the country. Hornell's (1910) account is based on an examination of a few lots of spat-collectors placed in Ennur backwaters, near Madras, during the months of the north-east monsoon of the year 1908, to ascertain the principal determining factors in oyster-spawning; his observations on the rate of growth were only incidental. Paul's (1942) study of the growth of this species, among other animals, deals with material from the Madras harbour. Although this species occurs in fair numbers and breeds well under the almost marine conditions of the harbour, it remains stunted and does not grow to the maximum size usually reached in estuaries and backwaters (vide Rao, 1951). Since it is well known that oysters of the same brood from the same locality exhibit a wide range of growth (Orton, 1937; Havinga, 1928 and Korringa, 1953) the maximum growth-rate alone, as given by previous workers for this species, will be of little significance. An attempt has been made here to study the maximum and the mean rates of growth of the spat and yearlings of the oysters in their natural environs, together with the possible effects of the fluctuating environmental factors upon the rate of growth.